The conceptual model of information confrontation of virtual communities in social networking services - Kateryna Molodetska; Yuriy Tymonin; Ihor Melnychuk (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Social networking services are one of the most popular mass media and are used as an effective tool for information confrontation due to their functional characteristics. Existing models of information confrontation take into account the redistribution between conflict parties of only one kind of resource, although in the social networking services there is a need to consider additional factors that determine the effectiveness of virtual communities’ opposition. A conceptual model of information confrontation of virtual communities in social networking services has been developed, and it includes three-layer dynamics of the number of actors, growth of information resources of virtual communities and dynamics of spending resources for the confrontation conduct. The model also takes into account the peculiarities of the antagonistic conflict of virtual communities’ actors through the choice of a differential equation that corresponds to the type of its dynamics. The offered conceptual model formalizes the behavior of virtual communities’ actors in the conditions of antagonistic conflict. At the same time, it allows to investigate the peculiarities of using different strategies to carry out the information fight of virtual communities in social networking services, to choose optimal strategies, to predict the development of conflicts in the information space and to develop effective measures to counter threats to the state’s information security.